Hubungan Brand Awareness Dalam Menentukan Keputusan Pembelian di Coffee Shop Teras Muzaka Lubuk Basung (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Teras Muzaka Lubuk Basung coffee shop is one of the coffee shops established in Lubuk Basung and has many customers. Based on observations made by the Teras Muzaka Lubuk Basung Coffee shop, it has several problems, including instability in the number of orders, consumers do not get an attractive impression when visiting, consumers only focus on one product so they do not recognize the Teras Muzaka Lubuk Basung Coffee shop brand, Teras Muzaka Coffee shop Lubuk Basung is not yet the main choice for consumers and there is a tendency for consumers to compare Teras Muzaka with other competing coffee shops.This type of research is classified as a quantitative research method with a causal associative approach. This research was conducted to see whether there is an influence of Brand Awareness on purchasing decisions at Teraz Muzaka Lubuk Basung, as well as to see the relationship between these two variables. The sampling technique used was purposive sampling. The number of samples was determined using the Slovin formula. The number of samples used was 377 respondents.Based on the research conducted, the following results were obtained: the level of respondents' achievement in the Brand awareness variable was 64% in the not good category and the purchasing decision variable was 73% in the quite good category. The results of the simple linear regression test obtained a calculated F value of 61.318 with Sig 0.000 < 0.05, so regression can be used. This means that brand awareness has a significant influence on purchasing decisions. The result of the regression coefficient equation is 0.538 with a sig value. 0.000 < 0.05. The R square value is 0.138, meaning that the Brand awareness variable has an influence of 13.8% on purchasing decisions at the Teras Muzaka Lubuk Basung Coffee shop and 86.2% is influenced by other variables not discussed in this research.